Deviant acts in the use of ChatGPT: An analytical study of student behaviour - Wahyu Purwasih; Ahmad Sahnan; Nadiya Takhsinia Bilqis; Mohamad Mabarun; Ahmad Bagus Romadhon (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Technological progress is indeed a necessity. However, the sophistication of existing technology is unfortunately not accompanied by the maturity of its users, especially students. Use ChatGPT in every task. Thus causing a decrease in creativity and a lack of originality in the work. The research method used is qualitative descriptive. Data were collected using participatory observation techniques, in-depth interviews, documentation, and focus group discussions. The results showed that the negative impact of using ChatGPT is over-reliance, which causes students to be unable to think critically, lack problem-solving skills, have decreased social interaction, and are vulnerable to receiving information bias. The treatment for students who are already addicted to using ChatGPT includes recognizing the signs of addiction that arise, collaborating with professional experts such as psychologists or counselors, training students to think critically and independently, and providing alternative activities that encourage them to participate in social activities. This research still needs improvement. So it needs some further development. These are some suggestions from this study: Investigate the psychological impact of students using ChatGPT, Design an Academic Curriculum by Collaborating with AI, and Develop an evaluation system that combines authentic tasks and the use of ChatGPT.